Primary amiloidosis: Amiloidosis primaria - Castillo-Velarde, Edwin Rolando (2019)
Amyloidosis constitutes a differential diagnosis in a patient with nephrotic syndrome. The presence of systemic and evolutive manifestations supports the possibility of primary amyloidosis. A review of the clinical is presented in relation to a case.